Simulation of the electromagnetic properties of silver nanostructures on the solid substrate in the air atmosphere - Mikitchuk, Alena P.; Kozadaev, Konstantin V. (Journal of the Belarusian State University. Physics, 2017)
Optical spectrum and electromagnetic field distribution for 2D-array of silver nanoparticles on the solid substrate of glass are simulated by means of CST Studio software. Design considerations based on the matching of nanoparticle shape, aspect ratio and surface occupation density are formulated for control optical extinction spectrum. It is shown, that surface plasmon resonance peak position can be controlled in the range from 350 to 750 nm by means of nanoparticle shape variation. Fine control of the spectral shape of surface plasmon resonance peak can be realized by variation of nanoparticle aspect ratio and surface occupation density. An approach to simulation of the 2D silver nanostructures on the solid substrate surface is proposed on the basis of the finite integral technique. Simulation of the 2D-array of silver nanoparticles on the solid substrate is performed. Simulation of both the macroscopic (optical extinction spectra) and microscopic (spatial distributions of an electromagnetic field within the nanostructure) properties of the 2D-array of silver nanoparticles is illustrated by several examples. The optical properties, spatial distributions of an electromagnetic field within nanoparticles of different shapes (in the form of sphere, cone, and cylinder) are compared for the nanostructures on the glass substrate in the air atmosphere. Interrelation between the electromagnetic field structure and the surface occupation density or the aspect ratio of a nanoparticle is investigated in detail. The spatial distribution of an electromagnetic field within the nanostructure is studied for different spectral positions on the surface plasmon resonance peak. Also, the nanostructures without interparticle interactions are studied. The influence of the nanoparticle aspect ratio on the properties of optical extinction spectra for the 2D-nanoarray is examined. In general, the possibility to vary the optical spectral properties by controlling shapes, surface occupation density, and aspect ratio of nanoparticles is demonstrated.
Keywords: 2D-array; silver nanoparticles; optical extinction spectrum; surface plasmon resonance